Where the legitimation of sustainable public procurements finds conflict: an analysis of public procurement agents’ perceptions on sustainable procurements - Euflausino, Mariana Aparecida; Mello, Gilmar Ribeiro de (Revista de Administração da UFSM, 2019)
The state has its purchasing power evidenced. Therefore, by using it strategically, it can influence the market, creating a demand for sustainable goods and services, through the inclusion of sustainable criteria in their purchasing and contracting process. On the other hand, the purchasing process has the action of public contracting agents as decisive element for the application of this process. Thus, it is relevant to know the perception of the agents on the subject, in view of possible obstacles to its implementation, even though the process is legitimized by State regulations. Therefore, the objective of this study was to analyze the perception of public contracting agents regarding sustainable public procurements and their application, by adopting a descriptive character with quantitative approach. The data were collected during the 2nd International Summit on Sustainable Public Contracting, held in Brasília, DF. The sample consisted of 77 public servants. The analysis used descriptive statistics and cluster analysis. The results indicate the possibility of inefficient training and qualification of the agents, as well as the recognition by the agents that the cultural factor is the main obstacle for the application of sustainable public procurements.